"To dream, or not to dream" – "Sofies Welt", eine philosophische traum-lese-reise - NEIS, Kathrin Svenja (Ondina - Ondine, 2019)
Jostein Gaarder’s philosophical novel Sophie’s World was extremely popular in the 1990s, not only among children. The essay seeks to trace the peculiarity of the text by focusing specifically on the aspect of the journey and the dream. In doing so, I argue that the very combination of these two elements in conjunction with the teaching of the history of philosophy reveals basic characteristics of narration itself, such as illusion and world construction. In addition to an ‘educational journey’, readers will thus experience the illustration of philosophical questions such as the ontological basic idea of the ‘world as a dream’.Keywords: philosophical novel, Constructivism, Ontology, Dream, Journey, Narration